Efekt sektorowy wskaźników finansowych przedsiębiorstw w krajach Unii Europejskiej - Koralun-Bereźnicka, Julia (Sectoral Effect in Financial Ratios of Selected European Union Countries, 2008)
The aim of the research is the analysis and classification of economic sectors in the EU countries based on a selection of financial ratios in enterprises. The analysis is meant to identify the occurrence of sector effect in the examined population. The methodology of the research involves multivariate statistical methods, including cluster analysis and multidimensional scaling. The main conclusion drawn from the research is confirming the influence of sector effect upon financial ratios as well as classifying the sectors according to their effectiveness and solvency.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 296-304